SISTEM INFORMASI PENJUALAN BARANG BERBASIS WEB PADA PT. CATUR DAYA PERSADA JAKARTA - Henny Destiana (Paradigma, 2014)
The need for fast and accurate information is huge. Various methods are used by the business to further promote their company, in addition to the old ways such as advertisements, banners, brochures and soon, internet media is used as a way to promote their products in order to increase sales. Internet is chosen as promotional media because it is more effectively and efficiently. PT Catur Daya Persada is a company engaged in the field of sales services, in running the business pretty face obstacles in delivering the goods which information is sent to the customer. Therefore, the author tries to create a website for PT Catur Daya Persada in order to increase the performance of the company. Freight information system is an application-based system created a website and a database containing goods as well as data transmission. So as to manage the data into reports and information in accordance with customer needs, the owner and administrator with more effective and efficient.